Ultrastructure of the calcium release channel of sarcoplasmic reticulum (The Rockefeller University Press, 1988)
This study is concerned with the characterization of the morphology of the calcium release channel of sarcoplasmic reticulum (SR) from fast- twitch skeletal muscle, which is involved in excitation-contraction coupling. We have previously purified the ryanodine receptor and found it to be equivalent to the feet structures, which are involved, in situ, in the junctional association of transverse tubules with terminal cisternae of SR. The receptor is an oligomer of a single high molecular weight polypeptide and when incorporated into phospholipid bilayers, has channel conductance which is characteristic of calcium release in terminal cisternae of SR. The purified channel can be observed by electron microscopy using different methods of sample preparation, with complementary views being observed by negative staining, double staining, thin section and rotary shadowing electron microscopy. Three views can be observed and interpreted: (a) a square face which, in situ, is junctionally associated with the transverse tubule or junctional face membrane; (b) a rectangle equivalent to the side view; and (c) a diamond shape equivalent to the side view, of which the base portion appears to be equivalent to the transmembrane segment. Negative staining reveals detailed substructure of the channel. A computer averaged view of the receptor displays fourfold symmetry and ultrastructural detail. The dense central mass is divided into four domains with a 2-nm hole in the center, and is enclosed within an outer frame which has a pinwheel appearance. Double staining shows substructure of the square face in the form of parallel linear arrays (six/face). The features of the isolated receptor can be correlated with the structure observed in terminal cisternae vesicles. Sections tangential to the junctional face membrane reveal that the feet structures (23-nm squares) overlap so as to enclose smaller square spaces of approximately 14 nm/side. We suggest that this is equivalent to the transverse tubule face and that the terminal cisternae face is smaller (approximately 17 nm/face) and has larger alternating spaces as a consequence of the tapered sides of the foot structures. Image reconstruction analysis appears to be feasible and should provide the three-dimensional structure of the channel.